Metal-Free Csp3–N Bond Cleavage of Amides Using tert-Butyl Hydroperoxide as Oxidant - Guo, Shengmei; Zhu, Zheng; Lu, Lin; Zhang, Wenbiao; Gong, Jiuhan; Cai, Hu (Synlett, 2015)
A mild and efficient protocol for the metal-free C–N bond-cleavage of amides has been developed. The methodology employs iodine as a catalyst to cleave the C(Me)–N bond of dimethylformamide or dimethylacetamide, providing novel access to methylene-bridged bis-1,3-dicarbonyl compounds instead of enol carbamates in the presence of tert-butyl hydroperoxide.
Keywords: metal-free; C–N bond cleavage; amides; dicarbonyl compounds; oxidation